Teacher preparedness for competency-based curriculum in Kenyan schools: training and perceptions prior to implementation - Nathan Maina Mwangi; Simon Karuku; Elizabeth Obura (Institute of Advanced Engineering and Science, 2026)
Pre-implementation training and teachers’ perceptions are critical factors influencing successful implementation of a new curriculum. This paper reports on some of the findings from a study that assessed the preparedness of primary school educators to implement the newly introduced competency-based curriculum (CBC) in Kenya. The study participants were primary school teachers and school heads drawn from 37 public elementary schools in Embu, Kenya. Using a mixed-methods approach, both qualitative and quantitative data were gathered through surveys, interviews, and observations. Qualitative data were analyzed using thematic analysis, whereas quantitative data were examined using descriptive and inferential statistics. The study revealed that 95% of teachers had been trained to implement CBC, and 65% of the teachers held negative perceptions toward the new curriculum. The study also established a weak but significant correlation (Spearman’s rho=0.268, p<0.05) between pre-implementation training and teachers’ perceptions on the CBC implementation. The findings suggest that continuous, structured in-service training is critical for CBC success, particularly in building competencies and improving teachers’ perceptions.